NHERI centrifuge facility: systems-scale hypergravity modeling in engineering and scientific research - DeJong, Jason T.; Wilson, Daniel W.; Martinez, Alejandro; Ziotopoulou, Katerina; Ham, Soo-Min; Boulanger, Ross W. (Frontiers in Built Environment, 2025)
The Natural Hazards Engineering Research Infrastructure facility at the University of California at Davis (UC Davis) is equipped with 9-m- and 1-m-radius geotechnical centrifuges that provide unique, world-class facilities for scaled modeling of complex systems. This national, open access research facility allows scientific and engineering communities to realize major advances in understanding, predicting, and improving the performance of civil infrastructure and natural systems. Large-scale centrifuge modeling of systems-level problems is particularly effective in advancing fundamental knowledge, upscaling and testing new technologies at the prototype scale, developing engineering analysis and design methods, and validating advanced computational models. The capabilities and unique role of large-scale centrifuge modeling are illustrated through four example research projects. These are followed by a discussion of envisioned future research directions and opportunities on how hypergravity modeling can be used to address natural and anthropogenic-induced loadings on civil infrastructure and natural systems.